The Influence of Practical Facilities on the Quality of Learning at State Vocational Schools - Handayani, Kristin; Kusumaningsih, Widya; Sudana, I Made (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Vocational education plays a crucial role in preparing skilled workers amidst the demands of Industry 4.0; however, limited practical facilities often hinder the quality of learning. This study examines the impact of practical facilities on the quality of learning in State Vocational High Schools in Blora Regency, based on data indicating that approximately 38% of facilities in several vocational schools do not meet the standards. This quantitative study, employing an ex post facto approach, involved 196 teachers as respondents. Data were collected using a Likert scale questionnaire and analyzed through descriptive statistics, prerequisite tests, and simple and multiple linear regression analysis with the help of SPSS 29.0. The study’s results showed that practical facilities had a positive and significant impact on learning quality, with a Pearson correlation coefficient of 0.926 (robust) and a determination coefficient (R²) of 0.857, indicating that practical facilities explained 85.7% of the variance in learning quality. This study suggests that improving practical facilities can significantly enhance the quality of learning. Educational institutions are expected to provide adequate practical facilities, enabling them to create a more effective learning environment and support the improvement of student competence in relevant fields.